Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Test: 12

Answer

$\frac{8-6\sqrt x+x}{8-2x}$

Work Step by Step

$\frac{4-\sqrt x}{4+2\sqrt x}\times\frac{4-2\sqrt x}{4-2\sqrt x}$ =$\frac{(4-\sqrt x)(4-2\sqrt x)}{(4-2\sqrt x)(4+2\sqrt x)}$ =$\frac{4(4-2\sqrt x)-\sqrt x(4-2\sqrt x)}{4^{2}-(2\sqrt x)^{2}}$ =$\frac{16-8\sqrt x-4\sqrt x+2x}{16-4(x)}$ =$\frac{2(8-4\sqrt x-2\sqrt x+x)}{2(8-2x)}$ =$\frac{8-4\sqrt x-2\sqrt x+x}{8-2x}$ =$\frac{8-6\sqrt x+x}{8-2x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.